Modelling of Thermodynamic Efficiency for Biomass Steam Gasification with In-Situ CO2 capture for Hydrogen Production - Ahmad, Murni M (2011)
Due to the intensive demand for alternative clean energy from renewable sources, the potential of converting biomass into hydrogen is currently under serious consideration. This potential is even more attractive with the abundant availability of agricultural wastes in Malaysia, a major palm oil producer. This work reports the mathematical modelling of thermodynamic efficiency for hydrogen production from biomass via steam gasification with in-situ carbon dioxide capture using CaO as sorbent. The model that includes the mass and energy balances for a specified flowsheet design incorporates the thermodynamic analysis approach based on the first law to identify potential improvement in the process via increasing its energy efficiency and sustainability. The influence of temperature, steam/biomass and sorbent/biomass ratios are profiled against the thermodynamic efficiency. The results show that the thermodynamic efficiency depends on feed stock quality and vary with the operating conditions. The model predicts an increment in the thermodynamic efficiency from 66.5 to 83.3% within the temperature range of 900 to 1100 K. Increasing either steam/biomass ratio or sorbent/biomass ratio also increases the thermodynamic efficiency. Furthermore, the maximum hydrogen purity of 81 mole% is predicted to occur at 950 K in the gasifier and can be enhanced to 99.9 mole% using a scrubber and a pressure swing adsorption unit after the gasifier. The results are compared with selected literatures and show good agreement.